"Innocent Young Girls": The Search for Female Provincial Leaders in China. (16th September 2022) - Chen, Minglu
Abstract: There are few women among China's local political leadership. Current scholarship on the topic co-locates women's political participation with the representation of other marginalized social groups. In particular, it is argued that female politicians are simply tokenistic representatives of the marginalized: female, intellectual, ethnic minority and non-Communist Party members. An examination of those women who have served in provincial leadership positions over the last two terms suggests that such a characterization is misleading. Rather, the evidence indicates that women have been appointed on the same grounds as male leaders in terms of age, education, CCP membership and experience. Gender disparities in the selection of provincial leaders are in fact considerably more nuanced and can be traced to the lack of institutionalized policies and processes as well as women's ongoing disadvantages in education, political networks and training.